ANALISIS PERENCANAAN DAN PENGENDALIAN MANAGEMENT DALAM PEMBERIAN PINJAMAN MODAL USAHA PADA PROGRAM KEMITRAAN USAHA KECIL (PKUK) PT. PUPUK SRIWIJAYA PALEMBANG - Ernawati .; Ade Inke Katherina (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
The purpose of this research is to discuss about management planning and control in Program Kemitraan Usaha Kecil (PKUK) PT. Pupuk Sriwijaya Palembang in terms of business capital management which Program Kementrian BUMN to help people economy through granting of rotating fund (capital) to support business contiunity especially UKM and Koperasi. The grant is only granted to UKM and Koperasi which are central business that needs to be developed by providing soft loans business funds, coaching and training in order to grow and compete in the global market. This research was conductes at PT. Pupuk Sriwijaya Palembang in Departemen PKBL part Kemitraan is located at Jalan Mayor Zen Palembang. The result showed that in lending capital only pursued management targets that let led to inefficient distribution of capital and make companies less throught in conductive credit analysis. This causes the non-performing loans of the assited partners. The management control of PKUK is also not going will because of the back of maximum monitoring and billing to the assisted partners. This it is expected that the management performance of PKUK PT. Pupuk Sriwijaya Palembang can perform better and selected business capital management in terms of lending to prospective partners, so that the disbursed capital is more effective and targeted, not merely fulfilling the obligation and forming a positive image of the company in the social environment.Keywords : Management planning and control, PKUK